WITHHOLDING TAX SYSTEM UNTUK PEMUNGUTAN PAJAK: UPAYA PENINGKATAN PENERIMAAN PAJAK VS INSTRUMEN TAX PLANNING - Dinik Fitri Rahajeng Pangestuti; Arum Puspita Wardhani (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2019)
Taxes are the greatest source of country income. The funds derived from the tax are used to perform the development of State infrastructure. Various efforts have been made by the Government to be able to set tax payments, one of which by implementing the withholding tax system. This system is expected to increase tax acceptance, but some parties actually utilize it in a tax planning strategy as an effort to streamline the tax burden to be paid. So far, tax revenues in Indonesia are still relatively low compared to the expected. Financial Minister of Indonesia, Sri Mulyani stated that the government can only collect tax revenues of 14.1% of the Indonesian Gross Domestic Product (GDP). Nevertheless, research proves that overall withholding tax system has been able to increase tax revenues in Indonesia both income tax and value added tax. Withholding tax system proved to have a positive impact in the taxation in Indonesia although it needs to be improved in these effectiveness and efficiency.